Lens parameters for Gaia18cbf: a long gravitational microlensing event in the Galactic plane - Kruszyńska, Katarzyna; Wyrzykowski, Lukasz; Rybicki, Kris A.; Maskoliūnas, M.; Bachelet, Etienne; Rattenbury, Nicholas James; Mróz, P.; Zieliński, P.; Howil, K.; Kaczmarek, Z.; Hodgkin, Simon T.; Ihanec, N.; et al. (Astronomy and astrophysics, 2022)
The timescale of a microlensing event scales as a square root of a lens mass. Therefore, long-lasting events are important candidates for massive lenses, including black holes.Here, we present the analysis of the Gaia18cbf microlensing event reported by the Gaia Science Alerts system. It exhibited a long timescale and features that are common for the annual microlensing parallax effect. We deduce the parameters of the lens based on the derived best fitting model. We used photometric data collected by the Gaia satellite as well as the follow-up data gathered by the ground-based observatories. We investigated the range of microlensing models and used them to derive the most probable mass and distance to the lens using a Galactic model as a prior. Using a known mass-brightness relation, we determined how likely it is that the lens is a main-sequence (MS) star. This event is one of the longest ever detected, with the Einstein timescale of days for the best solution and days for the second best. Assuming Galaxy priors, this translates to the most probable lens masses of and , respectively. The limits on the blended light suggest that this event was most likely not caused by a MS star, but rather by a dark remnant of stellar evolution.
Gesehen am 11.08.2022